Complex control of development in coordinating skills of students of UAB - Остапенко (Ostapenko U.) Юрій Олександрович (Slobozhanskyi Herald of Science and Sport, 2012)
<!–[if gte mso 9]> 1024x768 <![endif]–> This article presents a comprehensive monitoring and evaluation criteria to determine the development of test exercises coordination abilities in students 17–18 years UABD. Designed assessment criteria for determining the level of development of coordination abilities of seven motor tests for students-boys at the age of 17–18 years. Analyzed the dynamics of complex control development coordination abilities, entrants for the period 2008–2011 academic years. Practical application of the method of integrated control allows you to provide a qualitative assessment of the development of motor abilities of students, provides a timely opportunity to adjust teaching physical education. <!–[if gte mso 9]> Normal 0 false false false <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>